Analysis for Spatial Heterogeneity of Water Quality of Rivers in Mingcheng Town - ZHOU Xuexin; ZHAO Xiaochen; ZHANG Shu; GE Xiaoxia (Renmin Zhujiang)
To protect and improve the water environment,this paper takes rivers and Gaoming river in Mingcheng Town as research objects,researches the current status of the water environment of 36 monitoring sections,analyzes the spatial variation of six water quality indexes i.e.DO,CODMn,COD,BOD5,NH3-N and TP by GIS technique and mathematical statistics method,and discusses the influence of land use types on spatial variation of water quality.The results of research show that:the overall water quality of rivers in Mingcheng Town was poor.Water quality indexes showed significantly spatial variation,and the coefficient of variation of NH3-N and TP was higher than other water quality indexes.In terms of space,compared with other research units,R7 water quality was poorer.Part of the water quality indexes showed obvious spatial concentration and positive spatial autocorrelation.In wet season,there was a significant correlation between land use types such as vegetation,cultivated land and water area and water quality indexes.The agricultural runoff pollution and aquaculture pollution may be the important factors that affect water quality.In dry season,there was no obvious correlation of land use types with water quality indexes.The poor water quality may be caused by the domestic pollution sources,industrial pollution sources and agricultural non-point sources.